12 week PET-CT has low positive predictive value for nodal residual disease in human papillomavirus-positive oropharyngeal cancers. (October 2019) - Rulach, Robert; Zhou, Suyun; Hendry, Fraser; Stobo, David; James, Allan; Dempsey, Mary-Frances; Grose, Derek; Lamb, Carolynn; Schipani, Stefano; Rizwanullah, Mohammed; Wilson, Christina; Paterson, Claire
Highlights: 12-week surveillance PET-CT post-radiotherapy for patients with HPV positive disease has a PPV of 30%. 79.4% of HPV positive equivocal responders had no active disease in the neck after 6 months. No difference in survival was noted between HPV positive complete responders and equivocal responders. This patient group could be suitable for further surveillance instead of immediate neck dissections. Abstract: Objectives: Surveillance PET-CT scans at 12 weeks post-radiotherapy for head and neck cancer can be used to omit neck dissections with no detriment in overall survival. Human Papillomavirus (HPV) driven tumours behave differently on conventional imaging after radiotherapy but it is unknown if this effect is seen on PET-CT and if HPV status affects the accuracy of PET-CT. We aimed to determine the negative and positive predictive values (NPV and PPV) of 12 week surveillance PET-CT in HPV positive and negative tumours, and investigate predictors of relapse in equivocal responders. Materials and methods: A retrospective cohort study in a UK tertiary level oncology hospital, between 2013 and 2016 included adults with oropharyngeal squamous cell carcinoma, or HPV positive head and neck squamous cell cancers of unknown primary, treated with radiotherapy. Results: The PPVs of 12 week PET-CT in HPV positive and negative disease are 30% and 81.8% respectively (p < 0.01). The NPVs of 12 week PET-CT in HPV positive and negative disease are 92.9% and 55.6% respectively (p < 0.01). 67% of HPV positive patients with equivocal responses on 12 week PET-CT achieved complete response by 24 weeks. Equivocal responses in HPV positive disease had statistically similar survival to patients with complete responses. Comparing disease and imaging characteristics, there were no predictors of residual tumour. Conclusions: HPV positive tumours have a poor PPV of 30% on 12 week surveillance PET-CTs and take longer to achieve complete response. A period of further surveillance can be considered instead of an immediate neck dissection in this group of patients.